Roseovarius bejariae sp. nov., a moderately halophilic bacterium isolated from a hypersaline steep-sided river bed. - Castro, David J.; Gómez-Altuve, Andreína; Reina, José Carlos; Sampedro, Inmaculada; Llamas, Inmaculada; Rodríguez-González, Miguel Ángel; Sampedro, Inmaculada; Llamas, Inmaculada; Martínez-Checa, Fernando (Microbiology Society, 2020)
An aerobic, Gram-stain-negative ovoid, designated as strain A21T , was isolated using the dilution-to-extinction method from a soil sample taken from Rambla Salada, an athalassohaline habitat located in Murcia (south-eastern Spain). Strain A21T is nonmotile, has a respiratory metabolism and grows at NaCl concentrations within the range 0.5–15% (w/v) [optimum, 5% (w/v)], at 5–35°C (optimum, 28°C) and at pH 6–8 (optimum, pH 7.0). This strain is positive for catalase activity, oxidase activity and nitrate reduction. The 16S rRNA gene sequence indicates that it belongs to the genus Roseovarius in the class Alphaproteobacteria. The most closely related species are Roseovarius pacificus and Roseovarius halotolerans to which the strain A21T shows 16S rRNA gene sequence similarity values of 98.06 and 97.7%, respectively. The average nucleotide identity in blast and digital DNA–DNA hybridization values between strain A21T and R. pacificus LMG 24575T are 76.8 and 21%, respectively. The DNA G+C content based on the genome is 61.28mol%. The major fatty acids (>5% of the total fatty acids) of strain A21T are C18:1ω7c/C18:1ω6c and C16:0 . The only detected isoprenoid quinone in strain A21T is ubiquinone 10 (Q-10). The polar lipid profile contains phosphatidylcholine, phosphatidylethanolamine, phosphatidylglycerol and three unidentified polar lipids. Based on the phylogenetic, genotypic, phenotypic and chemotaxonomic data, the strain represents a novel species of the genus Roseovarius, for which the name Roseovarius bejariae sp. nov. is proposed. Strain A21T (=CECT 9817T =LMG 31311T ) is the type strain.
Keywords: Bacterias - Clasificación; Bacterias halofilas; Suelos - Salinidad; Roseovarius bejariae sp. nov.; Polyphasic taxonomy; Halophilic bacteria; Saline soil